Emendas participativas ao orçamento público: um estudo sobre essa prática no legislativo brasileiro - Cacciatori, Cassio Germano (2020)
Over time, representative democracy has been questioned by the growing distance between the yearnings of citizens and the actions of elected politicians. Social, political and economic concerns resulting from such distancing eventually produced new dynamics of organization and popular participation. One of the ways to make the approximation between representatives and represented possible is the participatory budget, an instrument that has already been used by the Executive of hundreds of Brazilian municipalities. But also in the Legislative, something similar has happened: parliamentarians have been presenting amendments to the public budget taking into account popular opinion, allocating resources in projects defined by the population itself or with its collaboration. This study aims to elaborate an overview of the participatory practices used by Brazilian legislators in the definition of amendments to public budgets. The research undertaken is descriptive and exploratory in terms of its objectives, and qualitative in its approach. Lnitially, a bibliographic and documentary survey was conducted to identify similar studies and to know the state of art of the subject. After an unsuccessful attempt to obtain data via the Access to Information Act, the next step was to build a questionnaire to obtain data from members of the Legislature of the Union, the States, the Federal District and the hundred municipalities with largest Gross Domestic Product (GDP) in the country. The questionnaire served to identify more than two dozen parliamentarians adhering to the participatory practices surveyed, which generated as a main result of the study an initial overview of the participatory practices that Brazilian lawmakers use as a means of amending public budgets. This adaptation of participatory budget for use in the deliberation of budget amendments confirms its dynamism as one of the most successful participatory institutions. The survey also pointed out that the majority of respondents prefer to use the Internet to encourage the population to decide which projects will benefit from amendments and that, even with social participation being encouraged, the legislators are responsible for the final decision on the projects contemplated with an amendment in almost all of the identified cases. Finally, a report was prepared with the results of the study, aiming to register, systematize and make its information available to everyone.